Incidence of Cervicitis in Infertile Women: A Study in Medical Center Clinic, Makassar City, Indonesia - Setiawati, Dewi; Rachma, Novianeu Salsabila (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
Infertility is a significant global health concern, yet the role of cervicitis as an independent risk factor remains inadequately explored. While previous studies have investigated various causes of infertility, limited research has specifically examined the combined effect of cervicitis and sperm abnormalities on reproductive outcomes. This study aims to determine the impact of cervicitis on infertility and assess its association with sperm abnormalities among married couples seeking conception. A cross-sectional study was conducted at the Wirahusada Medical Center Clinic, Makassar, Indonesia, involving 94 married couples undergoing routine fertility assessments. Cervicitis was diagnosed through endoscopic examination, while sperm abnormalities—including oligospermia, poor motility, and abnormal morphology—were identified via semen analysis following WHO 2021 standards. The odds ratio (OR) and Chi-Square test were used to analyze the relationship between cervicitis, sperm abnormalities, and infertility. Women with cervicitis had a lower pregnancy rate (25% vs. 75%), with an infertility risk 7.186 times higher (OR = 7.186). Men with sperm abnormalities also had a higher infertility risk (OR = 4.234). The highest risk (OR = 9.060) was in couples where both partners had these conditions. This study highlights the significant impact of cervicitis on female infertility, particularly when accompanied by sperm abnormalities. These findings underscore the need for integrated reproductive health strategies, including early screening and targeted interventions, to enhance pregnancy success rates among couples facing infertility.